Vitamin C intake and cognitive function in older U.S. adults: nonlinear dose–response associations and effect modification by smoking status - He, Xingchen; Lin, Yijia; Wu, Xinyi; Li, Min; Zhong, Tianyu; Zhang, Yanhong; Weng, Xuliang (Frontiers in Nutrition, 2025)
ObjectiveTo investigate the association between vitamin C intake and cognitive function in U.S. older adults, focusing on dose–response characteristics and effect modification of key subgroups.MethodsUtilizing data from the 2011–2014 National Health and Nutrition Examination Survey (NHANES), this cross-sectional study included 2,801 adults aged ≥ 60 years. Total vitamin C intake was assessed via standardized 24-h dietary recalls and supplement questionnaires. Cognitive function was evaluated using the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) Word Learning Test, Animal Fluency Test (AFT), and Digit Symbol Substitution Test (DSST). Multivariate adjusted linear regression models, smooth curve fitting, and stratified regression analyses were employed to examine associations and effect modification.ResultsOur analysis revealed a nonlinear dose–response relationship between vitamin C intake and cognitive performance. In fully adjusted models, participants in the highest intake quartile (Q4) showed significantly better performance on the Auditory Fluency Test (AFT; β = 1.11, 95% CI: 0.37–1.85) and the Digit Symbol Substitution Test (DSST; β = 3.35, 95% CI: 1.49–5.21) compared to those in the lowest quartile (Q1). Threshold analyses indicated that cognitive protection for DSST peaked at an intake of 500 mg/day, while AFT benefits plateaued at 120 mg/day. Stratified analyses further demonstrated that the cognitive benefits of vitamin C were more pronounced among smokers (DSST: β = 0.59 per 100 mg/day, p = 0.0009), with no significant associations observed in non-smokers.ConclusionVitamin C intake is associated with improved cognitive function in older U.S. adults, with distinct dose-dependent and domain-specific threshold effects. Smoking status significantly modifies this relationship, suggesting that personalized supplementation strategies targeting smokers may enhance cognitive protection.